Effects of Physical Exercises Alone on the Functional Capacity of Individuals with Obesity and Knee Osteoarthritis: A Systematic Review - Caiado, Vanessa Silva; Santos, Aline Cristina Gomes; Moreira-Marconi, Eloá; Moura-Fernandes, Marcia Cristina; Seixas, Adérito; Taiar, Redha; Lacerda, Ana Cristina Rodrigues; Sonza, Anelise; Mendonça, Vanessa Amaral; Sá-Caputo, Danúbia Cunha; Bernardo-Filho, Mario (Biology, 2022)
The association between obesity and knee osteoarthritis (KOA) is reported in the literature. The inflammatory factors described in obesity associated with mechanical overload on the knee joint lead to KOA development and reduced functional capacity in these individuals. Most physical exercise (PE) protocols associate a diet program to improve the functional capacity of individuals with concomitant KOA and obesity. There is a lack of published protocols performing PE alone, which would be without an associated diet program in individuals with both clinical conditions. In this systematic review, the authors summarize the effects of the application of PE alone, describing each protocol and reporting the improvement in the function of people with these clinical conditions. This investigation was conducted according to the PRISMA guidelines and registered in PROSPERO. Five databases (MEDLINE/PubMed, PEDro, Scopus, CINAHL and Web of Science) were used up to July 2022 and ten studies, including 534 participants, met the inclusion criteria. The PEDro scale, Cochrane collaborations and ROBINS-I tools were used to evaluate the methodological quality and risk of bias. It was concluded that PE performed alone seems to provide an improvement in the functional capacity of these individuals even without an associated diet plan in the condition of obesity.
Keywords: knee osteoarthritis; obesity; physical exercise alone; physical function; rehabilitation